(untitled) (International Association of Biologicals and Computational Digest, 2022)
Epipremnum aureum belonging to the family Araceae are most commonly known as Money plant. Epipremnum aureum species is one of the most popular houseplant and generally used for a ornamental purposes. It is a common indoor plant and has air purifying properties which removes air pollutants such as xylene, formaldehyde and benzne.. In this article, we review origin, distribution, morphological characters, Qualitative screening, ethnomedicinal uses and medicinal properties of Epipremnum aureum. Every part of the E.aureum possess antioxidant and antibacterial properties. It can also contain anti-malarial, anti-cancerous and wound healing etc properties. There are many more hidden properties in Epipremnum species that need to be exposed through using the scientific investigation to make it useful for the human health and environment.